Efektivitas Peran Guru Dalam Kurikulum Merdeka Belajar - Nurul Amelia; Shela Fahra Dilla; Siti Azizah; Zachra Fahira; Ahmad Darlis (Peneliti.net, 2023)
One of the important things in learning is the role of the teacher. However, along with the development of the world of education, the role of the teacher is very fundamental to be discussed, especially in the independent learning curriculum. The teacher is seen as the initiator in independent learning. Therefore, teachers should have the ability to be active, creative, innovative, enthusiastic and skilled in order to fulfill their role as facilitators who bring change to schools. This article was written with the aim of analyzing the effectiveness of the teacher's role in the independent learning curriculum used today. The data sources used are in the form of literature related to the theme, whether in the form of journals, articles, books, or other sources originating from the internet. The method used is the literature study method, namely by finding and collecting various related sources, then filtering them according to the theme presented.